2016
DOI: 10.1007/s12264-016-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Actin Aggregations Mark the Sites of Neurite Initiation

Abstract: A salient feature of neurons is their intrinsic ability to grow and extend neurites, even in the absence of external cues. Compared to the later stages of neuronal development, such as neuronal polarization and dendrite morphogenesis, the early steps of neuritogenesis remain relatively unexplored. Here we showed that redistribution of cortical actin into large aggregates preceded neuritogenesis and determined the site of neurite initiation. Enhancing actin polymerization by jasplakinolide treatment effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 81 publications
(103 reference statements)
1
27
0
Order By: Relevance
“…To determine whether PIs regulated actin aggregation and neuritogenesis, we first assayed whether PIP 3 , PI(3,4) P 2 or PI(4,5)P 2 co-localized with actin aggregates during early neurite initiation. Cultured hippocampal neurons were fixed 3-6 h after plating, at a developmental stage where they typically had one or two large actin aggregates underneath the plasma membrane, defined as stage 1b in our previous study [23] ( Figure 1F). Neurons were identified by immunostaining for the microtubule-associated protein 2 (MAP2), while filamentous actin (F-actin) was visualized using phalloidin.…”
Section: Pi(34)p 2 Co-localizes With Actin Aggregates During Neuritomentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether PIs regulated actin aggregation and neuritogenesis, we first assayed whether PIP 3 , PI(3,4) P 2 or PI(4,5)P 2 co-localized with actin aggregates during early neurite initiation. Cultured hippocampal neurons were fixed 3-6 h after plating, at a developmental stage where they typically had one or two large actin aggregates underneath the plasma membrane, defined as stage 1b in our previous study [23] ( Figure 1F). Neurons were identified by immunostaining for the microtubule-associated protein 2 (MAP2), while filamentous actin (F-actin) was visualized using phalloidin.…”
Section: Pi(34)p 2 Co-localizes With Actin Aggregates During Neuritomentioning
confidence: 99%
“…As compared to the last three stages of neuronal morphogenesis, which have been extensively studied [3][4][5][6][7][8][9][10][11][12][13], relatively little is known regarding the mechanism regulating neuritogenesis -the initial extension of neurites from the spherical soma [14][15][16][17][18][19]. Recent work from a number of laboratories, including our own, demonstrated a critical role of actin aggregation during neuritogenesis [20][21][22][23]. Using a combination of loss-and gain-of-function strategies, as well as pharmacological tools, these studies showed that the redistribution of evenly distributed cortical actin underneath the cell membrane into large actin aggregate(s) was required for neuritogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex feat is driven by neuronal polarization which causes an initial break in symmetry within an immature neuron, seamlessly followed by the two stages of neuritogenesis: neurite initiation followed by neurite elongation (4, 7, 8). Following neuronal polarization, actin aggregates form the sites of primitive neurites, precursors to the axon and dendrites (4, 9, 10). At these sites, actin rich filopodia and lamellipodia rapidly extend and retract before being stabilized by microtubule invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules are among the most prominent structural components found in growing and mature neuritic projections [4][5][6]. The microtubule-associated protein tau plays an important role in microtubule assembly and stabilization [7].…”
Section: Introductionmentioning
confidence: 99%